2018
DOI: 10.1038/s41437-018-0147-1
|View full text |Cite
|
Sign up to set email alerts
|

Multi-objective optimized genomic breeding strategies for sustainable food improvement

Abstract: The purpose of breeding programs is to obtain sustainable gains in multiple traits while controlling the loss of genetic variation. The decisions at each breeding cycle involve multiple, usually competing, objectives; these complex decisions can be supported by the insights that are gained by applying multi-objective optimization principles to breeding. The discussion in this manuscript includes the definition of several multi-objective optimized breeding approaches within the phenotypic or genomic breeding fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
94
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(94 citation statements)
references
References 73 publications
(77 reference statements)
0
94
0
Order By: Relevance
“…Accounting for within cross variance to measure the expected gain of a 437 cross in optimal cross selection was already suggested in Shepherd and Kinghorn (1998). More recently, 438 Akdemir and Sánchez (2016) and Akdemir et al (2018) accounted for within cross variance considering 439 linkage equilibrium between QTLs. Akdemir and Sánchez (2016) also observed that accounting for 440 within cross variance during cross selection yielded higher long term mean performance with a penalty 441 at short term mean progeny performance.…”
Section: Accounting For Within Family Variance In Optimal Cross Selecmentioning
confidence: 99%
See 3 more Smart Citations
“…Accounting for within cross variance to measure the expected gain of a 437 cross in optimal cross selection was already suggested in Shepherd and Kinghorn (1998). More recently, 438 Akdemir and Sánchez (2016) and Akdemir et al (2018) accounted for within cross variance considering 439 linkage equilibrium between QTLs. Akdemir and Sánchez (2016) also observed that accounting for 440 within cross variance during cross selection yielded higher long term mean performance with a penalty 441 at short term mean progeny performance.…”
Section: Accounting For Within Family Variance In Optimal Cross Selecmentioning
confidence: 99%
“…Optimal contribution 62 selection aims at identifying the optimal contributions ( ) of candidate parents to the next generation 63 obtained by random mating, in order to maximize the expected genetic value in the progeny ( ) under 64 a certain constraint on inbreeding ( ) (Wray and Goddard 1994;Meuwissen 1997;Woolliams et al 65 2015). Optimal cross selection, further referred as OCS, is an extension of the optimal contribution 66 selection to deliver a crossing plan that maximizes under the constraint by considering additional 67 constraints on the allocation of mates in crosses (Kinghorn et al 2009;Kinghorn 2011;Akdemir and 68 Sánchez 2016;Akdemir et al 2018). In the era of genomic selection, the expected 69 genetic value in progeny ( ) to be maximized is defined as the mean of parental GEBV ( ) weighted 70 by parental contributions , i.e.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…While they 101 applied this equation to the case of parental contribution (treated as a quantitative trait) correlated 102 with an agronomic trait of interest, the theory could be generalized to two or more traits in the 103 traditional sense. Additionally, Akdemir et al (2019) applied a multi-objective optimized 104 7 breeding strategy in simulations to select parent combinations and improve two unfavorably 105 correlated traits. This approach solves the multiple objective optimization problem of 106 maximizing the genetic gain of two or more traits while constraining inbreeding.…”
Section: Introduction 36mentioning
confidence: 99%